(untitled) (Sociologisk Forskning, 1994)
Alternative or Reconstruction? - On Haberm as criticism of Marx Should we understand Habermas’ works in social theory and politics as an alternative to or a reconstruction of Marx? I try in this article to present the possible arguments for both standpoints. It is shown that if we take our point of departure in Habermas’ distinction between ”labour” and ”interaction”, we must treat his writings as an alternative to Marx. If we, however, start out with his distinction between ”life world” and ”system”, then we must understand them as a reconstruction. In the first case it becomes clear that the concepts ”labour” and ”interaction” are opposites and can be used to ground opposite social scientific paradigms, but in the second case it becomes just as clear that Habermas’ criticism of the system’s colonisation of the life world is modelled after Marx’ criticism of political economy. Taken together, Habermas two forms of criticism of Marx leads him to transfer the Marxian form of criticism of modem society from the capitalistic economy to the paternalistic social state. That is, Habermas doesn’t locate reification in the capitalistic mode of production. In society of today reification is the product of the social state.